Analisis Tingkat Minat Masyarakat Pekanbaru Terhadap Mobile Banking BNI Menggunakan Pendekatan TAM - Ilham Aulia Aldrin; Zahara Zahara; Josephine Sudiman (Politeknik Negeri Padang, 2023)
This study aims to determine the level of public interest in using BNI Mobile Banking in Pekanbaru City. This research is supported by the Technology Acceptance Model (TAM) theory, while the variables used are perceived ease of use and perceived usefulness as independent variables, while BNI Mobile Banking user interest is the dependent variable. The population in this study were users of the BNI Mobile Banking application in Pekanbaru City and sampling was carried out using a non-probability sampling method with a method of determining the number of samples, namely using the lemeshow formula used to calculate samples with unknown populations. This study uses a quantitative approach with multiple linear regression analysis methods with a total of 100 respondents. This research data collection was carried out by distributing questionnaires online. The results of this study indicate that perceived ease of use has a positive and significant effect on user interest in the BNI Mobile Banking application in Pekanbaru City and perceived usefulness has no significant effect on user interest in the BNI Mobile Banking application in Pekanbaru City.